Efek Kausal Konsep Diri Akademik dan Minat Keguruan terhadap Ekspektasi Karier sebagai Guru dan Kaitannya dengan Sikap Profesionalisme Keguruan - Supriadi, I Gede Indra; Dantes, Nyoman; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2017)
This research aims at investigating: (1) the directÂ effect of career expectation as teacher (X3) on teaching professionalism attitude (X4), (2) the direct effect of academic self-concept (X1) on teaching professionalism attitude (X4), (3) the direct effect of teaching interest (X2) on teaching professionalism attitude (X4), (4) the direct effect of academic self-concept (X1) on career expectation as teacher (X3), (5) the direct effect of teaching interest (X2) on career expectation as teacher (X3), (6) the indirect effect of academic self -concept (X1) on teaching professionalism attitude (X4), (7) the indirect effect of teaching interest (X2) on teaching professionalism attitude (X4). The population of the research was 251 students of PGSD Undiksha. It was an ex-post factor research. The result of the research shows that: (1) there is a direct effect of 0.2971 from X3 on X4, (2) there is a direct effect of 0.2724 from X1 on X4, (3) there is a direct effect of 0.1706 from X2 on X4, (4) there is a direct effect of 0.3709 from X1 on X3, (5) there is a direct effect of 0.2084 from X2 on X3, (6) there is an indirect effect of 0.2496 from X1 on X4, (7) there is an indirect effect of 0.2914 from X2 on X4.